2003
DOI: 10.1212/01.wnl.0000044396.64752.4c
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of motor cortex excitability by pallidal stimulation in patients with severe dystonia

Abstract: GPi stimulation influences motor cortex excitability by a rapid modulation of thalamocortical outputs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 27 publications
5
37
0
1
Order By: Relevance
“…No significant differences were found in most tests among the three conditions, the only exception being a reduction in the SP duration. Similar absence of modification of SICI was reported by Kuhn et al (2003) during GPi DBS in patients with dystonia. However, switching off GPi stimulation led to an increase in motor threshold, and reduced the size of contralateral responses in the stimulus-response curves in relaxed muscles.…”
Section: Cortical Physiologysupporting
confidence: 86%
See 1 more Smart Citation
“…No significant differences were found in most tests among the three conditions, the only exception being a reduction in the SP duration. Similar absence of modification of SICI was reported by Kuhn et al (2003) during GPi DBS in patients with dystonia. However, switching off GPi stimulation led to an increase in motor threshold, and reduced the size of contralateral responses in the stimulus-response curves in relaxed muscles.…”
Section: Cortical Physiologysupporting
confidence: 86%
“…A different result was reported by Cunic et al (2002) who examined the effects of STN DBS on cortical excitability in 9 PD patients, using the same protocol that Chen et al (2001) and Kuhn et al (2003) used for the GPi. These authors found that resting SICI, studied with paired-pulse TMS at the interstimulus interval of 2 ms, was restored to normal levels in the 'on' condition.…”
Section: Cortical Physiologymentioning
confidence: 83%
“…The combination of DBS and TMS in PD is expected to provide information regarding the physiological mechanisms of extrapyramidal disorders. Some studies using TMS in DBS implanted patients have been reported without any serious complication or damage to the DBS system [6][7][8][9][10]. The device manufacturer, however, strictly indicates that TMS should not be administered to patients with an implanted DBS device due to the risk of brain damage [7].…”
Section: Introductionmentioning
confidence: 99%
“…The device manufacturer, however, strictly indicates that TMS should not be administered to patients with an implanted DBS device due to the risk of brain damage [7]. Although the safety or usefulness of TMS in patients with a DBS system implanted has been reported [1,[6][7][8][9][10], more systematic investigations are necessary before application of TMS to patients with an implanted DBS system becomes widespread. In this study, we systematically investigated the safety of TMS in patients with an implanted DBS device using a phantom simulation, and propose safety guidelines for the use of TMS.…”
Section: Introductionmentioning
confidence: 99%
“…105 Transcranial magnetic stimulation demonstrates decreased motor cortex excitability in dystonia patients, which can be reversed by GPi stimulation. 106 PET studies indicate higher glucose metabolism in bilateral lentiform nucleus of cervical dystonia patients, regardless of symptom laterality. 107 Reports on the application of DBS for the treatment of dystonia have primarily focused on GPi DBS, but other targets such as thalamic DBS have been tried, with less reliable results.…”
Section: Dystoniamentioning
confidence: 88%